Can singular examples change implicit attitudes in the real-world? - Roos, Leslie E.; Lebrecht, Sophie; Tanaka, James W.; Tarr, Michael J. (Frontiers in Psychology, 2013)
Implicit attitudes about social groups persist independently of explicit beliefs and can influence not only social behavior, but also medical and legal practices. Although examples presented in the laboratory can alter such implicit attitudes, it is unclear whether the same influence is exerted by real-world exemplars. Following the 2008 US election, Plant et al. reported that the Implicit Association Test or “IAT” revealed a decrease in negative implicit attitudes towards African-Americans. However, a large-scale study also employing the IAT found little evidence for a change in implicit attitudes pre- and post-election. Here we present evidence that the 2008 US election may have facilitated at least a temporary change in implicit racial attitudes in the US. Our results rely on the Affective Lexical Priming Score or “ALPS” and pre- and post-election measurements for both US and non-US participants. US students who, pre-election, exhibited negative associations with black faces, post-election showed positive associations with black faces. Canadian students pre- and post-election did not show a similar shift. To account for these findings, we posit that the socio-cognitive processes underlying ALPS are different from those underlying the IAT. Acknowledging that we cannot form a causal link between an intervening real-world event and laboratory-measured implicit attitudes, we speculate that our findings may be driven by the fact that the 2008 election campaign included extremely positive media coverage of President Obama and prominently featured his face in association with positive words – similar to the structure of ALPS. Even so, our real-world finding adds to the literature demonstrating the malleability of implicit attitudes and has implications for how we understand the socio-cognitive mechanisms underlying stereotypes.